The Innovation Model of Smartphone Adoption Among The Lecturers of Private Universities in Bandung - RACHMAWATI, Indira (Journal of Tourism Economics and Policy, 2021)
This study reveals innovations particularly related to the acceptance of mobile technology (smartphones) by lecturers. A smartphone is able to change the work performance of lecturers and academicians, especially with respect to technology. The purpose of this study is to determine whether the Job Relevance, observability, Compatibility, Personal demographics, Personal experience, Internal environment, and External environment have effects on attitude and its impact on the behavioral intention in the use of smartphones. The sampling technique used is non-probability sampling of 300 respondents who are lecturers of private universities in Bandung, by the deployment of questionnaires containing 27 question items. The data obtained from these respondents were processed using the technique of Partial Least Squares (PLS), and the results revealed that there is are influence of innovation factor on Attitude at 71% and there is an influence of Attitude on Behavioral Intention, amounting to 60.58%. There are five variables of innovation factor that affect the attitude, namely Job Relevance, observability, Compatibility, Personal experience, and Internal environment, while the other two variables, which do not affect the attitude, are the Personal Demographics and External Environment.